2016
DOI: 10.1080/01973533.2016.1215984
|View full text |Cite
|
Sign up to set email alerts
|

Whose Side Are You On? Exploring the Role of Perspective Taking on Third-Party’s Reactions to Workplace Deviance

Abstract: Original citation: Fiori, M., Krings, F., Kleinlogel, E. P. and Reich, Tara C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 64 publications
(77 reference statements)
1
13
0
4
Order By: Relevance
“…We suggest that observers who take the perspective of the instigator will respond positively toward the instigator. Extending Fiori et al’s (2016) findings that third-parties who make external attributions for the instigator of extreme forms of counterproductive work behavior (i.e., shooting a colleague and intoxication at work) are less likely to endorse punishment, we examine observer attributions and reactions toward both targets and instigators.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We suggest that observers who take the perspective of the instigator will respond positively toward the instigator. Extending Fiori et al’s (2016) findings that third-parties who make external attributions for the instigator of extreme forms of counterproductive work behavior (i.e., shooting a colleague and intoxication at work) are less likely to endorse punishment, we examine observer attributions and reactions toward both targets and instigators.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…I en kritik af O'Reilly og Aquinos (2011) model, argumenterer Fiori et al (2016) for, at relationer på en arbejdsplads, fx et venskab mellem to personer, kan påvirke vidners vurderinger, følelser og handlinger i situationer, hvor der sker kraenkende eller uretfaerdige handlinger. Fiori et al (2016) introducerer begrebet perspektivtagning, som er det faenomen, hvor mennesker prøver at forstå en anden persons mentale tilstand, følelser, holdninger og vurderinger (Fiori et al, 2016, s. 319). Forskerne argumenterer her for, at vidners reaktioner på afvigende adfaerd, fx kraenkende handlinger, også afhaenger af aktørperspektivet.…”
Section: Tentativ Vurderin G Af O'reilly Og Aquinos Model Ud Fra Sekundaer Empiriunclassified
“…Forskerne argumenterer her for, at vidners reaktioner på afvigende adfaerd, fx kraenkende handlinger, også afhaenger af aktørperspektivet. Resultater fra i alt tre eksperimenter (Fiori et al, 2016) støttede denne antagelse. Vidner, som blev bedt om at tage mobberens perspektiv, var mindre tilbøjelige til at synes, at vedkommende var ansvarlig for den kraenkende handling, og var derfor også mindre tilbøjelige til at straffe vedkommende.…”
Section: Tentativ Vurderin G Af O'reilly Og Aquinos Model Ud Fra Sekundaer Empiriunclassified
See 1 more Smart Citation
“…A handful of studies have shown that observers of downward abuse tend to respond in prosocial ways to mitigate the threat or repair the damage (e.g., Coyne et al, 2019; Hershcovis et al, 2017; Priesemuth, 2013; Priesemuth & Schminke, 2019). Yet other research suggests some observers may believe that the targets are deserving of the mistreatment (Mitchell et al, 2015) and take the perpetrator's perspective (Fiori et al, 2016) when the abuse is work related (Coyne et al, 2019). Given these mixed results, important questions remain unanswered: What may affect observers' judgment of teammate‐targeted leader abuse and their willingness to step in?…”
Section: Introductionmentioning
confidence: 99%